Who killed the writ of constitutional rights protection (acción de tutela) in terms of deprivation of liberty in Colombia? (2018)
The Colombian Constitutional Court declared 1988 that the conditions of its prisons were in a "state of unconstitutionality". With this declaration, the Court intended, not only to draw attention to its conditions, but to take the reins to overcome this s